The role of triglycerides in predicting new-onset arthritis in the general population over 45 years old: evidence from the China health and retirement longitudinal study - Ma, Weiwei; Chen, Honggu; Deng, Jing; Yuan, Qipeng; Li, Huanan (Frontiers in Endocrinology, 2025)
BackgroundArthritis is a common degenerative joint disease with a high prevalence especially in the elderly population. Due to its strong association with chronic pain and dysfunction, arthritis has become an important challenge in public health. Recent studies have shown that triglyceride (TG) levels, as key metabolic markers, may play an important role in the pathogenesis of arthritis, and its associated inflammatory response may accelerate joint degeneration and inflammatory process.ObjectiveBased on the above findings, the aim of this study was to investigate the association between baseline TG levels and the incidence of arthritis in adults aged 45 years and older, utilizing data from the China Health and Retirement Longitudinal Study(CHARLS).MethodsThis study utilized the CHARLS from 2011 to 2018, which included 7,551 participants aged 45 years and older. The association between TG levels and new-onset arthritis was assessed by logistic regression modeling, adjusting for demographic and health-related variables. The potential role of HDL-C, LDL-C, and BMI in the TG-arthritis association was further assessed by mediation analysis, which decomposed the association into direct and indirect effects.ResultsDuring the study period, 3,363 participants (44.5%) developed arthritis. Higher TG levels were significantly associated with arthritis risk, with an 8% increase in arthritis risk for each interquartile range (IQR) increase in TG (OR=1.08; 95% CI, 1.039-1.137.) Interquartile analyses of TG levels showed a significant dose-response trend (P trend <0.05), suggesting that the risk of arthritis tended to rise progressively with higher TG levels. Mediation analysis further revealed that HDL-C mediated approximately 43.5% of the TG-arthritis association, suggesting an important role of HDL-C in the metabolic pathway of arthritis development.ConclusionElevated TG levels were significantly associated with an increased risk of arthritis, and this association was partially mediated by HDL-C. The findings suggest that interventions targeting reduced TG levels and enhanced HDL function may have potential value in arthritis prevention. Future studies should focus on lipid metabolism intervention strategies to reduce arthritis risk and delay disease progression, providing a new scientific basis for arthritis management.